2019
DOI: 10.23910/ijbsm/2019.10.4.2011a
|View full text |Cite
|
Sign up to set email alerts
|

Post-submergence Nitrogen Fertilizer Management for Enhancing Rainfed Lowland Rice Productivity in Eastern India

Abstract: Flashflood in rainfed lowlands seriously affect rice crop establishment and cause severe yield losses. Survival of new flood tolerant rice varieties (Swarna-Sub1, Samba Mahsuri-Sub1, IR64-Sub1, etc.) developed through introgressing the submergence tolerance gene SUB1into mega rice varieties of South Asia is substantially higher than that of non-Sub1 varieties under flooding stress. This has been consistently reflected in a yield advantage of 1 to 3 t ha-1. Submergence tolerance and productivity of these Sub1 v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 32 publications
(58 reference statements)
1
2
0
Order By: Relevance
“…Higher grain yield with foliar application of nitrogen might be due to higher values of growth parameter which might have resulted in higher capture of solar energy and hence led to enhanced values of yield attributing characters, that ultimately resulted in higher grain yield. Similar results were also reported by Behera et al (2019).…”
Section: Grain Yieldsupporting
confidence: 92%
See 2 more Smart Citations
“…Higher grain yield with foliar application of nitrogen might be due to higher values of growth parameter which might have resulted in higher capture of solar energy and hence led to enhanced values of yield attributing characters, that ultimately resulted in higher grain yield. Similar results were also reported by Behera et al (2019).…”
Section: Grain Yieldsupporting
confidence: 92%
“…Among nitrogen levels, N B resulted in maximum number of tillers m -2 and it was statistically at par with those under N M and N MA at both the locations (Table 4). Behera et al (2019) also reported higher number of tillers hill -1 under higher doses of nitrogen as compared to lower doses.…”
Section: Number Of Tillers M -2mentioning
confidence: 83%
See 1 more Smart Citation